Isolation and potency of Actinomycetes from rhizosphere of nutmeg (Myristica fragrans Houtt) - Ferymon Mahulette; Esti Utarti; Tri Santi Kurnia (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
Nutmeg (Myristica fragrans Houtt) is commonly cultivated by people in the forests of Moluccas Islands. This plant grows well on relatively infertile soil types. This is presumably due to the presence of symbiotic microbes in the root of nutmeg. The research aimed to isolate, characterize and test the potential of Actinomycetes from rhizosphere of nutmeg. Soil sample were taken from the nutmeg forest in Ambon Island. The Actinomycetes isolation using humic acid vitamin, continued with yeast malt agar (YMA) media. The testing of antibacterial and antifungal activities using YMA media, while cellulolytic activity, phosphate solubilizing, and xylanolytic activity using carboxyl methyl cellulose, Picovskaya agar, and birchwood agar or oat spelt xylan agar. A total of 12 isolates of Actinomycetes were isolated and dominated by Streptomyces with various types of aerial mycelia. The substrate mycelium looks brown and cream, while the aerial mycelium looks white and gray. These isolates had the highest inhibitory power against Escherichia coli and Fusarium oxysporum with indexes of 16.5 mm and 16.0 mm, respectively. The other isolates have the ability of cellulolytic, phosphate solubilizing, and xylanolytic with indexes 3.26, 3.87, and 1.2, respectively. The Actinomycetes isolates that were found can be used as starter to improve the biofertilizer formula for nutmeg.